Resilience Analysis of MSME Employees’ Work Ethic During and After the COVID-19 Pandemic: A Chow Test Approach - Wawan Sadtyo Nugroho; Barkah Susanto; Muhamad Wahid Ibrahim; Ravindra Ardiana Darmadi; Wahyu Anggit Prasetya (www.amertainstitute.com, 2025)
The COVID-19 pandemic has significantly disrupted the operations of Micro, Small, and Medium Enterprises (MSMEs), especially in tourism-related regions such as Magelang. These disruptions not only affected business continuity but also increased stress levels among employees. This study aims to analyze the resilience of the work ethic of MSME employees during and after the pandemic using the Chow-Test. The theoretical framework integrates Affective Events Theory, the Transactional Stress Model, and Human Capital Theory to examine how challenge and hindrance stressors influence discretionary behaviors (citizenship and counterproductive behavior), with emotional reactions and work experience as mediating and moderating variables. A stratified random sampling technique was employed to collect primary data from 385 MSME owners and employees in Magelang. Data was analyzed using Structural Equation Modeling (SEM) and Chow-Test. The findings confirm that employee work ethic, particularly citizenship behavior, demonstrated strong resilience across both pandemic and post-pandemic periods. This supports the hypothesis that there is no significant difference in work ethic between the two periods. However, limitations include the geographic focus on one region and reliance on self-reported data. Future research should explore broader regions and consider longitudinal methods. This study provides practical insights for MSMEs to sustain performance through employee resilience in times of crisis.